THE RELATIONSHIP BETWEEN STRESS, ANXIETY, DEPRESSION AND MEDICATION ADHERENCE BEHAVIOR IN PATIENTS WITH EPILEPSY : A SYSTEMATIC REVIEW - Aulia Fajri, Azda; Hartono, Budi; Priscika Putri , Deby; Azhari, Ririn; Merisa L, Bella; Ananda, Astrid; Syarfina, Afdila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: While epilepsy is a disorder characterized by unprovoked seizures, epileptic status refers to recurrent seizures without any improvement in between episodes or seizure activity that does not improve on its own.Aims : This systematic review is to review the association of stress, anxiety, depression and medication adherence behavior in patients with epilepsy.Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 415 articles, whereas the results of our search on SAGEPUB brought up 573 articles, our search on SCIENCE DIRECT brought up 600 articles. The results of the search conducted for the last year of 2014 yielded a total 285 articles for PubMed, 275 articles for SAGEPUB and 391 articles for SCIENCE DIRECT. In the end, we compiled a total of  5 papers, 3 of which came from PubMed, 1 of which came from SAGEPUB and 1 of which came from SCIENCE DIRECT. We included five research that met the criteria.Conclusion: In summary, the anxiety, stress or depression can be the appear at epilepsy patients as the absence of the adherence of epilepsy therapeutic.